2009
DOI: 10.1007/s00122-009-1204-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-based distance measures for grouping of germplasm and prediction of hybrid performance in maize

Abstract: Grouping of germplasm and prediction of hybrid performance and heterosis are important applications in hybrid breeding programs. Gene expression analysis is a promising tool to achieve both tasks efficiently. Our objectives were to (1) investigate distance measures based on transcription profiles, (2) compare these with genetic distances based on AFLP markers, and (3) assess the suitability of transcriptome-based distances for grouping of germplasm and prediction of hybrid performance and heterosis in maize. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 19 publications
1
93
0
1
Order By: Relevance
“…Besides metabolite profiling, there are other promising genomics data sources with the potential to enhance the prediction accuracy of hybrid performance exploiting, for instance, structural variation (30) or transcriptome profiling (31). It would be of interest to integrate these data sources into the existing genomic selection models to increase the accuracy of prediction of hybrid performance for unrelated genotypes.…”
Section: Expanding the Search For Promising Heterotic Patterns Towardmentioning
confidence: 99%
“…Besides metabolite profiling, there are other promising genomics data sources with the potential to enhance the prediction accuracy of hybrid performance exploiting, for instance, structural variation (30) or transcriptome profiling (31). It would be of interest to integrate these data sources into the existing genomic selection models to increase the accuracy of prediction of hybrid performance for unrelated genotypes.…”
Section: Expanding the Search For Promising Heterotic Patterns Towardmentioning
confidence: 99%
“…Additionally, the identity, the genetic function and interaction of specific genes associated with heterosis of different traits is mostly unknown. More detailed information may be obtained by inspection of other molecular traits, like transcript or metabolite levels, which integrate genetic and environmental influences [17], [18]. The first complementary testing of large-scale genomic and metabolite data to predict important agronomical traits in hybrid maize test-crosses concluded that the prediction accuracies of heterotic traits in adult maize plants using metabolite profiles of the young leaves were only slightly lower than with Small Nucleotide Polymorphisms (SNPs), although metabolites represent approximately 300 times smaller number of variables compared to SNPs [19].…”
Section: Introductionmentioning
confidence: 99%
“…This has fostered the proposal that more bio-logically meaningful markers need to be exploited for this purpose. Therefore, it has been suggested that parental differences in gene expression levels from a genomewide perspective (transcriptome) will likely produce more reliable markers for the prediction of heterosis, and indeed, some promising results were obtained (Stupar et al, 2008;Swanson-Wagner et al, 2009;Frisch et al, 2010;Thiemann et al, 2010). Nonetheless, trans-criptome-based molecular makers are expensive to develop and, at the current stage, unrealistic to be readily used by breeders.…”
Section: Discussionmentioning
confidence: 99%